Knowledge and prevention of child sexual abuse among mothers in Akuku-Toru local government area, Rivers State, Nigeria: a descriptive cross-sectional study - Nwadiuto, Ifeoma Christiana; Briggs, Nduye Christie Tobin; Nduka, Ijeoma; Pius, Ositadinma Mberekpe (International Journal Of Community Medicine And Public Health, 2025)
Background: Child sexual abuse (CSA) remains a pervasive public health challenge globally and in Nigeria. Mothers, as primary caregivers, play a crucial role in CSA prevention. This study assessed knowledge and preventive practices regarding CSA among mothers in Akuku-Toru local government area, Rivers State, and examined their associations with selected demographic variables. Methods: A descriptive cross-sectional study was conducted among 364 mothers selected using multi-stage sampling. Data were collected using structured interviewer-administered questionnaires. Chi-square tests were performed to examine associations between demographic variables (age, education level, and employment status), knowledge of CSA, and preventive practices. Statistical significance was set at p<0.05. Results: Awareness of CSA was high (98.6%), but only 63.4% could identify signs of abuse. Mothers with tertiary education were significantly more likely to identify CSA indicators (χ2=21.62, df=6, p=0.0014). Age was significantly associated with having educated their child about CSA (χ2=36.18, df=3, p<0.001). Notably, mothers who recognized signs of CSA were more likely to have educated their children (χ2=34.09, df=2, p<0.001). However, 86.6% of respondents had not received formal training on CSA prevention. Conclusions: While general awareness of CSA is high, practical knowledge and preventive behavior remain suboptimal. Maternal education and age influence CSA-related knowledge and actions. Strengthening formal CSA education for mothers and integrating it into community and health education programs are critical for effective prevention.